Methods of products reliability evaluation based on the results of tests and operation - Козлюк, І. О.; Коваленко, Ю. Б. (Science-based technologies, 2018)
The article proposes methods for determining the characteristics of reliability indicators of functional systems of aviation equipment, based on the use of the exponential distribution, the probability-physical model of failures. This evaluation of the method determines the confidence probability and the accuracy of the evaluation of the reliability index of functional systems. The assessment of the level of reliability and its analysis are presented based on the results of tests and diagnostics of aviation equipment. Also, the data processing reliability components of aircraft for a certain period of operation. The initial data processing, the initial stage of evaluation, was performed for the initial and subsequent period of operation. The processing of the next stage was carried out by adding to the data volume of the preliminary stage new data obtained at the stage estimated by adjusting the content of the previous period database and recalculating the new value.